Predicting falls in older adults: an umbrella review of instruments assessing gait, balance, and functional mobility - Jepsen, D. Beck; Robinson, Katie; Ogliari, Giulia; Montero-Odasso, M.; Kamkar, N.; Ryg, J.; Freiberger, Ellen; Tahir, Masud (BMC Geriatrics, 2022)
Background: To review the validated instruments that assess gait, balance, and functional mobility to predict falls in older adults across different settings. Methods: Umbrella review of narrative- and systematic reviews with or without meta-analyses of all study types. Reviews that focused on older adults in any settings and included validated instruments assessing gait, balance, and functional mobility were included. Medical and allied health professional databases (MEDLINE, PsychINFO, Embase, and Cochrane) were searched from inception to April 2022. Two reviewers undertook title, abstract, and full text screening independently. Review quality was assessed through the Risk of Bias Assessment Tool for Systematic Reviews (ROBIS). Data extraction was completed in duplicate using a standardised spreadsheet and a narrative synthesis presented for each assessment tool. Results: Among 2736 articles initially identified, 31 reviews were included; 11 were meta-analyses. Reviews were primarily of low quality, thus at high risk of potential bias. The most frequently reported assessments were: Timed Up and Go, Berg Balance Scale, gait speed, dual task assessments, single leg stance, functional Reach Test, tandem gait and stance and the chair stand test. Findings on the predictive ability of these tests were inconsistent across the reviews. Conclusions: In conclusion, we found that no single gait, balance or functional mobility assessment in isolation can be used to predict fall risk in older adults with high certainty. Moderate evidence suggests gait speed can be useful in predicting falls and might be included as part of a comprehensive evaluation for older adults.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Accidental Falls; Fall Prediction; Function; Gait; Balance; Older Adults; Umbrella review